Integrative analysis of transcriptome and metabolome profiling uncovers underlying mechanisms of the enhancement of the synthesis of biofilm in Sporobolomyces pararoseus NGR under acidic conditions - Dandan Wang; Nan Zeng; Chunji Li; Chunwang Li; Yunjiao Wang; Bin Chen; Jiajia Long; Ning Zhang; Bingxue Li (Microbial Cell Factories)
Abstract Background Sporobolomyces pararoseus is a well-studied oleaginous red yeast that can synthesize a variety of high value-added bioactive compounds. Biofilm is one of the important biological barriers for microbial cells to resist environmental stresses and maintain stable fermentation process. Here, the effect of acidic conditions on the biosynthesis of biofilms in S. pararoseus NGR was investigated through the combination of morphology, biochemistry, and multi-omics approaches. Results The results showed that the acidic environment was the key factor to trigger the biofilm formation of S. pararoseus NGR. When S. pararoseus NGR was cultured under pH 4.7, the colony morphology was wrinkled, the cells were wrapped by a large amount of extracellular matrix, and the hydrophobicity and anti-oxidative stress ability were significantly improved, and the yield of intracellular carotenoids was significantly increased. Transcriptome and metabolome profiling indicated that carbohydrate metabolism, amino acid metabolism, lipid metabolism, and nucleic acid metabolism in S. pararoseus NGR cells were significantly enriched in biofilm cells under pH 4.7 culture conditions, including 56 differentially expressed genes and 341 differential metabolites. Conclusions These differential genes and metabolites may play an important role in the formation of biofilms by S. pararoseus NGR in response to acidic stress. The results will provide strategies for the development and utilization of beneficial microbial biofilms, and provide theoretical support for the industrial fermentation production of microorganisms to improve their resistance and maintain stable growth.